INTRODUKSI KAPAL FIBERGLASS DAN MANAJEMEN KEMITRAAN PRODUKSI LOIN TUNA - Akhmad Mansyur; La Anadi (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2015)
This paper is directed generally loin crease the production capacity of loin tuna as excellent potential acceleration of development Southeast Sulawesi. These efforts are pursued through the introduction of fiberglass boats based on fishing partnerships that an increase in the welfare of a sustainable society. In particular, aimed at improving the system of industrial fleet loin tuna, repair fishing partnership system, and increase the ability of employees in the field service fleet industry professionals. Methods of achieving the intended objectives, done through technical training in the marine capture fisheries, and apprenticeship in industries loin and ship building fiberglass. In addition, done with coaching, supervision of the target group, the provision of technology support, and resolving business is built. The approach used is konvergensy, implementary and developmentally. The results achieved are catching tuna fishermen are able to process their catch into loin in each capture site. Loin tuna quality of type A can still be maintained up to the shelter as a benefit of the method of packaging and the use of fiberglass boats which provide a prediction accuracy of landing. Finally, entrepreneurs can of tuna has produced as many as three people by promoting a partnership with local government of Southeast Sulawesi Province and loin tuna industry in Buton as the acquirer organization.Keywords : fiberglass boat, loin tuna, partnership management